Creating smart enterprises : leveraging cloud, big data, web, social media, mobile and IoT technologies - Kale, Vivek (Boca Raton, FL : CRC Press, 2017)
"This book guides IT and business executives through the technologies that create an intelligent, agile, and competitive enterprise. It examines social, contextual, search, and physical intelligence, and the technologies that emulate them. Each technology is covered in-depth and shown how at work in an intelligent enterprise."--Provided by publisher.
chapter VUCA Ecosystem / Vivek Kale -- chapter Aligning Business and IT Strategy / Vivek Kale -- chapter Enterprise Security / Vivek Kale -- chapter Process-Driven Organization / Vivek Kale -- chapter Analytics / Vivek Kale -- chapter Cloud Computing Basics / Vivek Kale -- chapter Big Data Computing / Vivek Kale -- chapter Web Applications / Vivek Kale -- chapter Social Networks / Vivek Kale -- chapter Mobile Applications / Vivek Kale -- chapter Internet of Things (IoT) Technologies / Vivek Kale.
Keywords: Information technology -- Management; Technological innovations -- Management